Nationalism in La Guerre's Poeme by Louise Ackermann - Putri, Fadhilah; Evi Rosyani Dewi; Wahyu Tri Widyastuti (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2022)
This study aims to describe the forms of nationalism in the poem La Guerre by Louise Ackermann. This study uses the theory of forms of nationalism according to Taguieff, they are nationalisme ethnique (ethnique nationalism), nationalisme civique (civique nationalism) and nationalisme culturel (cultural nationalism) which are contained in his book entitled La Revanche du Nationalisme. This research method is a qualitative descriptive analysis with flow model of analysis according to Miles and Huberman which includes three components of analysis, there are data reduction, data presentation, and drawing conclusions or verification which is carried out by flowing or interconnected and continuous with concurrent data collection process. The results of this study indicate that there are twenty-five (25) data in poetry that indicate forms of nationalism. In detail, there are twenty-four (24) quotations that have the form of nationalisme civique (civique nationalism), five (5) quotation that have the form of nationalisme culturel (cultural nationalism), and three (3) quotations that have the form of nationalisme ethnique (ethnic nationalism).